Development planning in Sabah - Rabe, Noor Suzilawati (IIUM Press, 2017)
This book entitled “Development Planning in Sabah” is a book that describes the development and planning practices in the state. The book starts with a discussion on early planning and development of Sabah during before the independence. The next chapter on planning and development framework in Sabah, the book illustrates Sabah from the perspective of Malaysia’s planning system. Discussions on planning and development division, statutory provision as well as on the preparation process of local plan or also known as planning scheme in Sabah are also included in this chapter. Furthermore, this book also discusses on the development control in Sabah. Development control is a legal procedure that has provided local authorities with the jurisdiction responsibility to translate ideas and policies of town and country planning into reality. It is also a process which consists of both the making of development plans and the practice of development control by local planning authorities. The processes included preparing and implement that plan through development plans, granting or refusing planning permission in their areas. Overall, this book discusses on development planning system in Sabah.